Problem Based Learning on Newton's Law: Can It Improve Student Creativity? - Nurlaili Wisda Agustin*; Sarwanto Sarwanto; Agus Supriyanto (Universitas Syiah Kuala, 2021)
Creativity is important in facing a challenging future life. Therefore, current learning is focused on not only values but also soft skills such as student creativity. Few teachers provide opportunities for students to develop their creativity in the classroom. This creativity can be developed and trained through various learning strategies. Probem-based learning was chosen in this study as a means to increase students' creativity through two learning methods, experiment and demonstration. This study seeks to determine the effect of experimental and demonstration methods with problem-based learning model on student creativity on Newton's law material. The subjects included 72 tenth-grade science students in Surakarta, Central Java. They were selected using the purposed random sampling technique where out of 8 tenth-grade science students in SMA Al Islam, Surakarta, 2 classes that met the research category were selected. This experimental study collected the data using pretest and posttest for cognitive data and questionnaire using a Likert scale for student creativity data. Data were analyzed descriptively through independent sample t-test. The results showed that both methods through problem-based learning model had a significant effect on the level of student creativity. From the characteristics of the methods and the number of students in the high creativity category, experimental method is superior to be applied. It is implied that teachers can use the experimental method with problem-based learning model in Newton's law to develop student creativity soft skills.